2022
DOI: 10.3390/ani12233374
|View full text |Cite
|
Sign up to set email alerts
|

Too Much of a Good Thing: Rethinking Feed Formulation and Feeding Practices for Zinc in Swine Diets to Achieve One Health and Environmental Sustainability

Abstract: The objectives of this review were to summarize current knowledge of Zn in swine nutrition, environmental concerns, potential contribution to antimicrobial resistance, and explore the use of alternative feeding strategies to reduce Zn excretion in manure while capturing improvements in productivity. Zinc is a required nutrient for pigs but is commonly supplemented at concentrations that greatly exceed estimated requirements. Feeding pharmacological concentrations of Zn from ZnO to pigs for 1 to 2 weeks post-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 160 publications
0
14
0
Order By: Relevance
“…It is this need to balance the conflicting requirements of improved agricultural productivity and reduced environmental contamination that has caused some authors to recommend targeted mineral treatments at specific growth stages. 7 The present study assumed that all of the zinc consumed would be excreted, and whilst this is approximately correct, based on reported results, 6 it is slightly conservative and will lead to a small overestimation of zinc loadings to soils from this source because some zinc (<20%) is retained by the piglets.…”
Section: Discussionmentioning
confidence: 79%
“…It is this need to balance the conflicting requirements of improved agricultural productivity and reduced environmental contamination that has caused some authors to recommend targeted mineral treatments at specific growth stages. 7 The present study assumed that all of the zinc consumed would be excreted, and whilst this is approximately correct, based on reported results, 6 it is slightly conservative and will lead to a small overestimation of zinc loadings to soils from this source because some zinc (<20%) is retained by the piglets.…”
Section: Discussionmentioning
confidence: 79%
“…Minimising the oxidative stress of pigs in intensive production systems is essential for optimising health and productivity, which contributes to achieving pork production goals through One Health and environmental sustainability [105]. A more holistic approach should be considered in herd health management of modern high-profiling sows, using PFAs with antioxidant properties in the swine industry in a routine program.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on investigating the most ideal prevention strategy for PWD. In view of the increasing resistance to antibiotics and the limitation of their use in pig diets [19,20], pig nutrition plays a key role in future prevention strategies [55,56]. For example, previous studies reported the beneficial effects of adding vegetable oils to weaners' diets against pathogens, including E. coli, which can cause gastrointestinal diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The use of zinc oxide (ZnO) as a feed additive has been commonly proposed for the prevention of PWD in piglets. Based on recent regulations from 2022, the application of dietary ZnO in weaning feed has been forbidden in the European Union (EU) to reduce the negative environmental consequences of pig manure in agricultural soils [19]. Due to modern consumer demands and public health awareness, restrictions on the use of antibiotics as growth promoters in pig diets have also been proposed and applied [20].…”
Section: Introductionmentioning
confidence: 99%